Eastern Mediterranean Quaternary paleoclimates from pollen and isotope records of marine cores in the Nile Cone Area - Cheddadi, Rachid; Rossignol-Strick, M (Paleoceanography, 1995)
Pollen spectra from three eastern Mediterranean cores have been used to document the paleoclimates of the Levantine Basin borderlands over the last 250 kyr to establish the relationship between this regional climate data set and the global climate as recorded by foraminiferal δ18O and to compare it with proximal land pollen records. Core MD 84 642 with eight sapropels covers the last two climatic cycles up to the early Holocene, MD 84 627 with four sapropels goes back to 125 kyr, and MD 84 629 with one sapropel covers the last 70 kyr. The sedimentation rate decreases from core 629, located at the shallowest depth beneath the Nile River plume, to cores 627 and 642. During the interglacials defined by a low 18O/16O ratio, the abundance of tree pollen is maximum and points to an optimum Mediterranean climate with greatest humidity, including some summer rainfall. During glacial maxima, with highest 18O/16O ratio, the pollen abundance is high for steppe and semidesert plants and low for trees, indicating a definitely more arid, more continental, and probably colder climate. The variations of pollen abundance occur in phase with those of the foraminifer δ18O record. This signifies that the regional climate of the Levantine Basin borderlands had the same temporal pattern as the global ice volume documented by the ice volume curve.
Keywords: climate; Eastern Mediterranean; Evergreen and deciduous forests; isotopic stratigraphy (voyant); pollen spectra